DIPLOMASI PERDAGANGAN INDONESIA DAN PAKISTAN PERIODE 2017-2019. Studi Kasus: Respon Indonesia Terhadap Rencana Kebijakan Pelarangan Vanaspati Ghee - Mohammad Nabil Hibatullah; Asep Kamaluddin Nashir (Dauliyah: Journal of Islam and International Affairs, 2021)
Indonesia and Pakistan have a trade history that can be said to be potentially and beneficial for both parties. One of the potential sectors and mainstay of Indonesia in Pakistan is the palm oil sector. However, a plan to ban palm oil products in Pakistan could threaten the sustainability of cooperation and disrupt Indonesia’s trade balance. Various attempts were made by the Indonesian government through a number of ways so that the planned ban was stopped and cooperation between the two parties can run smoothly again and is expected to develop in the future.